2019
DOI: 10.5897/jabsd2019.0354
|View full text |Cite
|
Sign up to set email alerts
|

The influence of solvents polarity on physicochemical properties and oil yield extracted from pumpkin (Cucurbita maxima) seed

Abstract: The effect of solvent polarity, polar and non-polar solvents, on pumpkin (Cucurbita maxima) seed oil yield and quality based on selected physicochemical properties was investigated. Five different solvents, like petroleum ether, hexane, cyclohexane, acetone and ethanol were used on a laboratory scale in this study. Results showed that both physicochemical properties and oil yield extracted from the pumpkin seed were influenced by solvent polarity. Oil yield ranged from 4.12 to 27.93%, with higher yield registe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…Specifically, the use of hexane solvent resulted in the highest iodine value of 3.02 g/100 g, whereas petroleum ether yielded a lower value of 2.05 g/100 g. The iodine value is a measure of unsaturation and serves as an indicator of the amount of double bonds present in the oil, which is related to its susceptibility to oxidation. This finding is consistent with previous research conducted by Lesten and Kingsley [30], who also reported a difference in iodine values between hexane-extracted oil and petroleum-extracted oil from pumpkin seeds.…”
Section: Iodine Valuesupporting
confidence: 93%
See 2 more Smart Citations
“…Specifically, the use of hexane solvent resulted in the highest iodine value of 3.02 g/100 g, whereas petroleum ether yielded a lower value of 2.05 g/100 g. The iodine value is a measure of unsaturation and serves as an indicator of the amount of double bonds present in the oil, which is related to its susceptibility to oxidation. This finding is consistent with previous research conducted by Lesten and Kingsley [30], who also reported a difference in iodine values between hexane-extracted oil and petroleum-extracted oil from pumpkin seeds.…”
Section: Iodine Valuesupporting
confidence: 93%
“…Additionally, unsaturation in the fatty acid chain enhances the cold flow property and offers better stability and a longer shelf life to the biodiesel [37]. Similar results have also been reported for para-rubber seed oil [38] and pumpkin oil [30] extracted using different solvents. Journal of Sustainable Bioenergy Systems…”
Section: Effect Of Solvent Type On Fatty Acid Composition Of Wpl Oilsupporting
confidence: 70%
See 1 more Smart Citation